Factors that influence customer loyalty towards Telekom Malaysia Berhad Business Sales, Negeri Sembilan / Siti Nor Ain Shariffudin - Shariffudin, Siti Nor Ain (Faculty of Business and Management, 2007)
Telekom Malaysia (TM) Berhad is the largest telecommunication company a leading regional information and communication groups, offers a comprehensive range of communication and services and solution in fixed-line, mobile, data and broadband in Malaysia. It is a near monopoly on the fixed line network and has a considerable market share of the mobile communication market after its acquisition with Celcom and X-pack. It has an Internet service provider subsidiary (TM Net) offering narrowband and broadband connectivity. Broadband connectivity is trough DSL under TM Net's Streamyx brand. Due to its near monopoly of the last mile connections, TM Net is now sole DSL broadband provider in the country.